Employee Social Skills as an Antecedent to Knowledge Sharing Behavior in Kenyan Universities - Biwott , G.; Maru , L.; Limo , P. (African Journal of Education,Science and Technology (AJEST), 2019)
This research paper addresses academic staff at universities Social skills as an emotional intelligence drive for modern universities in Kenya in having knowledge to explore any inherent understanding and intelligence-sharing behavioral dimension. Social skills are emotional social feelings according to their individual responses as they understand and know one another as Universities strive for improved knowledge. Explanatory study was used to target a population of 6,423 academic staff at Kenyan universities in Nairobi County. Although the social awareness behaviors of universities are widely known, more insights need to be drawn into the benefits of knowledge sharing behavior in order to evaluate its effect, given that social awareness acknowledges one’s effect on others and uses this extent of intuition to drive decisions on how they affect others ’ emotions. Social skills enhance the knowledge sharing behavior of academic staff in modern universities as confirmed by this study since the regression results indicated that social skills are significant at (β = 0.10, p<0.05) in advancing of knowledge sharing behaviours.